Intermittent Short Atrioventricular Delay in a Dual Chamber Pacemaker During Acute Pulmonary Edema - Ravi Vazirani; Miriam García Cocera; David Calvo (Annals of Noninvasive Electrocardiology)
ABSTRACT We present the case of an 80‐year‐old female with acute pulmonary edema and a dual chamber pacemaker with intermittent short AV delays in the surface ECG after blocked premature atrial contractions (PACs). The behavior was consistent with the programmed Window of Atrial Rate Acceleration Detection (WARAD) and did not require further parameter modifications. As most cardiologists and emergency department physicians are not familiar with brand‐specific algorithms, we believe that this case report will make these noncompetitive atrial pacing algorithms more accessible to non‐cardiologists.